Tunable micro-nano laser based on perovskite phase change material and preparation method thereof
By using perovskite materials as both gain dielectric and phase change material, combined with vertical resonant cavity design, the problem of difficulty in realizing multi-wavelength tunability of existing lasers is solved, and wide range tuning of laser wavelengths and high-efficiency laser output is achieved, with relatively high-quality laser output. Low laser threshold and high stability.
Patent Information
- Application Number
- CN202411691416.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing perovskite-based lasers usually operate at fixed wavelengths, which are difficult to meet the needs of multi-wavelength tunable laser sources. Traditional phase change materials lack light gain characteristics, which limits their application potential in lasers.
Dynamic tuning of the spectrum and efficient laser output are achieved by using perovskite materials as both gain dielectric and phase change materials, combined with vertical resonant cavity design.
Achieves wide range tuning of laser wavelengths, with low laser thresholds, high stability and low cost, suitable for a variety of types of tunable micro-nano laser applications.
Smart Images

Figure CN119496045A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of micro-nano optoelectronics, and relates to a tunable micro-nano laser based on perovskite phase change material and a preparation method thereof. Background Art
[0002] Perovskite semiconductors have attracted extensive attention in the field of optoelectronic devices in recent years due to their high photoluminescence quantum efficiency, adjustable band gap, narrow radiation spectrum and other characteristics. Especially in the application of micro-nano lasers, perovskite materials are regarded as ideal gain media for building the next generation of lasers due to their high optical gain and low lasing threshold. At present, perovskite-based lasers have made certain progress in the fields of distributed feedback (DFB) lasers, Fabry-Perot (FP) cavities, photonic crystals and vertical cavity surface emitting lasers (VCSELs). However, these lasers usually operate at fixed wavelengths, which makes it difficult to meet the needs of optical communications, tunable displays and sensors for multi-wavelength tunable laser sources.
[0003] In recent years, researchers have also conducted research on wavelength tunable lasers. One is to use a variety of materials or alloys with different band gaps to achieve the regulation of laser wavelength (patent CN202311571819.9, Fundamental Research2021,1,684-690). Although the wavelength tuning range is wide, the material selection and preparation are complex, and the growth regulation needs to be precisely controlled. In addition, compatibility issues between different materials (such as lattice matching, thermal expansion coefficient differences, etc.) will also affect the performance and stability of the device; the other is to transform and redesign the laser micro-nano resonant cavity, but this method can adjust the output wavelength range is small, the mechanical stability during the adjustment process is poor, the adjustment conversion efficiency is slow, the manufacturing is complex, and the price is expensive.
[0004] Compared with traditional semiconductor lasers, the scheme of using phase change materials (PCM) to achieve spectral tuning has attracted attention in recent years. For example, materials such as chalcogenide glass and vanadium dioxide (VO2) are widely used in optical switches and reconfigurable optical devices due to their adjustable dielectric constant. However, these traditional phase change materials lack optical gain characteristics, which limits their application potential in lasers. Therefore, the development of phase change materials with adjustable dielectric constant and optical gain has become an important research direction for realizing tunable lasers.
[0005] The unique phase transition characteristics of perovskite materials provide a possibility for this challenge. For example, organic-inorganic halide perovskites (such as CH3NH3PbI3, MAPbI3) can undergo a phase transition between orthorhombic phase and tetragonal phase in a specific temperature range (such as 130K to 160K), accompanied by significant changes in dielectric constant and optical gain. This phase change process can not only achieve spectral tuning through temperature regulation, but also maintain the efficient gain performance of the material, making it show great potential in building tunable lasers. In addition, the preparation process of perovskite materials is simple and has a low cost advantage, which can significantly reduce the difficulty of manufacturing complex photonic devices. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a tunable micro-nano laser based on perovskite phase change material and a preparation method thereof. By using perovskite material as both a gain medium and a phase change material, combined with a vertical resonant cavity design, dynamic tuning of the spectrum and efficient laser output are achieved.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A tunable micro-nano laser based on perovskite phase change material, the tunable micro-nano laser comprises a substrate I and a bottom distributed Bragg reflector II, a gain medium layer III and a top reflector IV arranged on the substrate I from bottom to top. The gain medium III is a perovskite material with crystal phase transition characteristics.
[0009] The substrate I is a material that is transparent to the pump light and the emission light or has very little loss. Optionally, the substrate I is made of quartz, silicon dioxide, indium tin oxide (ITO), polyimide (PI), polyethylene glycol (PET), etc.
[0010] Furthermore, if the substrate I is a material with relatively low loss, such as PI, the specific material of the gain medium layer III needs to be considered for selection to reduce the light loss generated by the substrate, and the thickness is 250 to 500 nm.
[0011] The bottom distributed Bragg reflector II is formed by alternating high refractive index layers and low refractive index layers. A layer of high refractive index material and a layer of low refractive index material form a cycle. The reflectivity of the high reflection area of the Bragg reflector is not less than 99%.
[0012] Optionally, the material of the high refractive index layer is one of tantalum pentoxide, hafnium dioxide, titanium dioxide, zinc sulfide, and gallium arsenide, and the material of the low refractive index layer is one of silicon dioxide, magnesium fluoride, and indium phosphide. The overall distributed Bragg reflector II has a thickness of 0.5 to 2.5 μm.
[0013] Furthermore, the number of pairs of high refractive index layers and low refractive index layers of the distributed Bragg reflector II is 5-20, and the high reflectivity region (reflectivity>99%) of the formed distributed Bragg reflector II should cover the photoluminescence spectrum region of the gain medium III.
[0014] Furthermore, by optimizing 1-3 pairs of alternating layers of high refractive index layers and low refractive index layers close to the substrate I of the bottom distributed Bragg reflector II, the transmittance of the pump light is made greater than 80%.
[0015] Furthermore, since the low refractive index material combines well with the gain medium III and has a large refractive index contrast, the distributed Bragg reflector II is designed so that the low refractive index layer contacts the gain medium III and the high refractive index layer contacts the substrate I.
[0016] The gain medium layer III is a perovskite thin film layer with a crystal phase transition characteristic, specifically, it can realize reversible transition between different crystal phases within a specific temperature range. The crystal phase transition is accompanied by significant changes in dielectric constant, optical gain and refractive index, thereby giving the perovskite material a spectral tuning function in the laser resonant cavity.
[0017] Furthermore, the thickness of the perovskite film layer is 100-500 nm to ensure optimal optical confinement and gain matching in the tunable micro-nano laser.
[0018] Furthermore, the material composition of the perovskite film layer is ABXn, wherein A is a monovalent cation, B is a divalent metal cation, X is an anion, and n is a positive integer.
[0019] Furthermore, the A is a cesium ion (Cs + ), methylamine ion (MA + ), formamidinium ion (FA + ), ethylamine ion (EA + ); B is lead ion (Pb 2+ ), tin ions (Sn 2+ ), Germanium ions (Ge 2+ ); X is a chloride ion (Cl - ), bromide ion (Br - ), iodide ion (I - )
[0020] The top reflector IV is composed of a metal film with a thickness of 50-200 nm to ensure that it has high reflectivity and stable optical performance within the target wavelength range, and the reflectivity in the photoluminescence spectrum region of the gain medium III is not less than 99%.
[0021] Furthermore, the metal is one of gold, silver, aluminum, or a mixture thereof. The specific preparation method of the metal film includes, but is not limited to, magnetron sputtering, thermal evaporation, or electron beam evaporation to ensure high quality and uniformity of the film.
[0022] A method for preparing a tunable micro-nano laser based on perovskite phase change material, comprising the following steps:
[0023] Step 1: Pretreatment of substrate I.
[0024] At room temperature, the substrate I is placed in acetone and isopropanol for ultrasonic cleaning for 5-15 minutes. Then it is rinsed with pure water or deionized water to remove the residual cleaning solution. It is then dried with a nitrogen stream to ensure that there is no water stain on the surface of the cleaned wafer. The cleaned substrate I is placed in an ultraviolet ozone cleaning machine and cleaned with oxygen plasma for 5-15 minutes to improve the adhesion to the distributed Bragg reflector II.
[0025] Step 2: Prepare the bottom distributed Bragg reflector II.
[0026] Step 2.1: Use magnetron sputtering or plasma enhanced chemical vapor deposition to alternately deposit multiple periods of high and low refractive index dielectric layers on the surface of substrate I to form a distributed Bragg reflector II, where the high refractive index layer is in contact with substrate I, and the top layer of distributed Bragg reflector II is a low refractive index layer.
[0027] Step 2.2: wipe the upper surface of the Bragg reflector II with ethanol for multiple times, then rinse off the residual ethanol with deionized water, blow dry with a nitrogen stream, and transfer to a UV ozone cleaning machine for oxygen plasma cleaning for 10-20 minutes to improve the adhesion to the perovskite film layer.
[0028] Step 3: Prepare the perovskite gain medium layer III.
[0029] A one-step solution deposition method is used to prepare a gain medium layer III on the surface of a Bragg reflector II, including the steps of preparing a perovskite precursor solution, adding an anti-solvent by spin coating to induce crystallization, and thermal annealing.
[0030] Step 4: Prepare top reflector IV.
[0031] The top reflector IV is prepared on the surface of the gain medium layer III by magnetron sputtering, thermal evaporation or electron beam evaporation.
[0032] Furthermore, the preparation process of the perovskite precursor solution is as follows: the precursor materials, such as PbI2, MAI, etc., need to be weighed according to the stoichiometric ratio, and the precursor materials are dissolved in N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO) or a mixed solvent of the two, and the precursor concentration is 0.2-2 M. Stir at 60-100°C until the solution is completely clear, and filter using a polyvinylidene fluoride (PVDF) syringe filter to remove impurities.
[0033] Further, the spin coating process of adding anti-solvent to induce crystallization by spin coating method is as follows: substrate I is fixed on a glue spreader, 20 μL-50 μL precursor solution is drawn using a pipette, and evenly dripped on the center of substrate I. The perovskite precursor solution is spin-coated onto a distributed Bragg reflector II at a speed of 3000-5500rpm for 30-70 seconds. Anti-solvent (such as one of toluene, chlorobenzene, and ether) is added dropwise to induce perovskite crystallization and enhance film quality in the 5th to 20th second after spin coating begins, and the amount of anti-solvent is 0.1-1ml. The quality and thickness of the film are controlled by adjusting the rotation speed, time, amount of dripping, and time of anti-solvent dripping.
[0034] Furthermore, the thermal annealing treatment is specifically as follows: after the spin coating and anti-solvent dripping process are completed, the film is immediately transferred to a heating table at 80-120° C. for thermal annealing for 5-15 minutes.
[0035] The design principle and innovation of the present invention are:
[0036] By using perovskite materials as both gain media and phase change materials, making full use of the significant changes in dielectric constants and optical gain of perovskite materials in different crystalline states, and combining them with the careful design of the vertical resonant cavity, dynamic tuning of the spectrum and efficient laser output can be achieved. Different from traditional tunable lasers that usually require the use of gain media and tuning elements separately, combining the gain medium and phase change material into one greatly simplifies the structure of the device. It not only reduces the size and complexity of the device, but also improves the stability and reliability of the device, providing new ideas for the field of optoelectronic device integration.
[0037] The beneficial effects of the present invention are:
[0038] (1) The present invention proposes to use perovskite materials as both gain media and phase change materials, thereby achieving wide-range tuning of laser wavelengths. The tuning range can reach several nanometers or even wider, meeting the needs of various application scenarios for lasers of different wavelengths.
[0039] (2) The present invention has a lower laser threshold and can achieve laser emission at a lower pump energy, thereby reducing the power consumption of the laser and improving energy utilization efficiency.
[0040] (3) The present invention exhibits high stability. During long-term continuous operation or multiple phase change cycles, the laser performance can remain stable, ensuring the reliability and service life of the laser.
[0041] (4) The design method of the present invention has a certain degree of versatility. Different perovskite phase change materials and laser structure parameters can be selected according to specific needs, and it is suitable for various types of tunable micro-nano laser applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a schematic diagram of the structure of the tunable micro-nano laser based on perovskite phase change material of the present invention.
[0043] Figure 2 The present invention is a flow chart for preparing a tunable micro-nano laser based on perovskite phase change material.
[0044] Figure 3 is a curve showing the change of optical properties of the perovskite phase change material of the present invention in different phases; Figure 3 (a) is the refractive index, Figure 3 (b) in the figure is the PL spectrum.
[0045] Figure 4 The output spectrum curves of the laser in the present invention under different working conditions (including different pump powers and different phase change states); Figure 4 (a) shows the variation of the emission spectrum of the perovskite material with the pump power when it is in the tetragonal phase; Figure 4 (b) in the figure shows the variation of the emission spectrum of the perovskite material in the orthorhombic phase with the pump power.
[0046] Figure 5 This is a graph showing the laser stability test results of the present invention.
[0047] Specific implementation method
[0048] The present invention will be further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0049] Example 1
[0050] This embodiment provides a tunable micro-nano laser based on perovskite phase change material and a preparation method thereof.
[0051] Optionally, taking iodine lead methylamine perovskite MAPbI3 as an example, the schematic diagram of the micro-nano laser structure is as follows: Figure 1As shown. Substrate I is quartz glass; distributed Bragg reflector II is made of 12 pairs of tantalum pentoxide / silicon dioxide materials stacked together, with a total thickness of 2.38μm; perovskite gain medium layer III is a 300nm thick MAPbI3 perovskite layer; top reflector IV is a 100nm thick gold reflective layer.
[0052] The preparation flow chart of this embodiment is as follows Figure 2 As shown, the following steps are included:
[0053] Step 1: At room temperature, ultrasonically clean the substrate I quartz glass in acetone, isopropanol, and deionized water for 10 minutes. Dry with a nitrogen stream to ensure that there is no water stain on the surface of the cleaned wafer. Place the cleaned quartz glass in a UV ozone cleaning machine and clean it with oxygen plasma for 10 minutes.
[0054] Step 2: Use magnetron sputtering to alternately deposit 12 cycles of tantalum pentoxide / silicon dioxide dielectric layers to form the bottom distributed Bragg reflector II. Wipe the upper surface of the Bragg reflector II with ethanol, then rinse with deionized water, dry with nitrogen flow, and transfer to a UV ozone cleaner to be cleaned with oxygen plasma for 15 minutes to improve the adhesion to the perovskite film.
[0055] Step 3: A 1.2 M precursor solution (1:1 molar ratio of PbI2 and CH3NH3I) was prepared in DMF. The prepared solution was magnetically stirred overnight at room temperature in a nitrogen-filled glove box, then filtered with a polyvinylidene fluoride syringe filter (0.45 μm) and placed on a hot plate at 100°C for 1 hour. The MAPbI3 layer was prepared by a one-step solution deposition method. 40 μL of the precursor solution was drawn using a pipette and evenly dropped on the center of the distributed Bragg reflector II. The perovskite precursor solution was spin-coated onto the distributed Bragg reflector at a speed of 5100 rpm for 30 seconds. 0.2 mL of toluene was dropped on the distributed Bragg reflector 5 seconds after the start of spin coating. Finally, it was placed on a hot plate at 100°C for thermal annealing for 15 minutes.
[0056] Step 4: The prepared sample with perovskite film (substrate I, Bragg reflector II, gain medium layer III) is quickly placed in the vacuum transition chamber of the magnetron sputtering equipment, and a 100 nm gold layer is deposited on the perovskite film by magnetron sputtering as the top reflector IV.
[0057] In this example, MAPbI3 perovskite undergoes a phase transition between tetragonal and orthorhombic states between 130-160 K, and this phase change leads to substantial modulation of the refractive index and photoluminescence spectrum, e.g. Figure 3 The complex refractive index of the MAPbI3 layer in the orthorhombic phase and the tetragonal phase was measured using variable angle ellipsometer (VASE), as shown in Figure 3(a). The material has a relatively high refractive index over a wide wavelength range in both states, which allows for efficient confinement and modulation of light on a subwavelength scale. Figure 3 (b) shows the photoluminescence spectra of MAPbI3 film in tetragonal and orthorhombic states. The photoluminescence spectrum (PL) of the tetragonal state has two peaks at around 740nm and 787nm, and the PL peak center of the orthorhombic state is around 790nm. The changes in the PL peaks in the two states indicate that the material has the potential to be used as a tunable laser gain medium.
[0058] The performance of tunable micro-nano lasers based on perovskite phase change materials is shown in Figure 2. Figure 4 The wavelength of the laser in the tetragonal phase is 790.6 nm, the wavelength of the laser in the orthogonal phase is 799.7 nm, and the average quality factor of the laser in the two phases is about 1136.
[0059] Figure 5 The lifetime of a tunable micro-nano laser (VCSEL device) under continuous pulse excitation (405nm, 130fs, 8kHz) is shown. The tunable micro-nano laser is optically pumped to 1.1F th (F th represents the threshold pump flow rate) and records the integrated radiation intensity over time. 80% lifetime (T 80 ) is defined as the time it takes for the output intensity to drop to 80% of the initial power. Figure 5 It can be seen that the laser intensity decreases relatively slowly, and at 125 minutes (T 80 >2h / 5.76×10 7 After the pump pulse, it maintained 80% of the initial level, proving that the tunable micro-nano laser has good operational stability.
[0060] Example 2
[0061] A tunable micro-nano laser based on perovskite phase change material and a preparation method thereof.
[0062] Optionally, the substrate I is quartz glass; the distributed Bragg reflector II is composed of 10 pairs of titanium dioxide / silicon dioxide materials stacked together, with a total thickness of about 2.04 μm; the perovskite gain medium layer III is a 180 nm thick CsPbI3 perovskite layer; the top reflector IV is a 60 nm thick silver reflective layer. The schematic diagram of the micro-nano laser structure can be found in Figure 1 ( Figure 1 The number of distributed Bragg reflector layers is only a schematic diagram and does not represent the actual number of layers).
[0063] The preparation flow chart of this embodiment can be found in Figure 2 , including the following steps:
[0064] Step 1: At room temperature, ultrasonically clean the substrate I quartz glass in acetone, isopropanol, and deionized water for 10 minutes. Dry with a nitrogen stream to ensure that there is no water stain on the surface of the cleaned wafer. Place the cleaned quartz glass in a UV ozone cleaning machine and clean it with oxygen plasma for 10 minutes.
[0065] Step 2: Use magnetron sputtering to alternately deposit 10 cycles of titanium dioxide / silicon dioxide dielectric layers to form the bottom distributed Bragg reflector II. Wipe the upper surface of the Bragg reflector II with ethanol, then rinse with deionized water, dry with nitrogen flow, and transfer to a UV ozone cleaner to be cleaned with oxygen plasma for 15 minutes to improve the adhesion to the perovskite film.
[0066] Step 3: A 0.4 M precursor solution (the molar ratio of CsI and PbI2 is 1:1) was prepared in DMSO. The prepared solution was magnetically stirred overnight at 70°C in a nitrogen-filled glove box, then filtered with a polyvinylidene fluoride syringe filter (0.2 μm) and placed on a hot plate at 70°C for 1 hour. 30 μL of the precursor solution was drawn using a pipette and evenly dropped on the center of the distributed Bragg reflector II. The perovskite precursor solution was spin-coated onto the distributed Bragg reflector at a speed of 3000 rpm for 30 seconds. 0.6 mL of toluene was dropped on the distributed Bragg reflector 10 seconds after the start of spin coating. Finally, it was placed on a hot plate at 80°C for thermal annealing for 5 minutes.
[0067] Step 4: The prepared sample with perovskite film (substrate I, Bragg reflector II, gain medium layer III) is quickly placed into the chamber of the electron beam evaporation equipment, and a 60nm silver layer is deposited on the perovskite film by electron beam evaporation as the top reflector IV.
[0068] The laser wavelength of the tunable micro-nano laser based on CsPbI3 is adjustable between 724.1 and 733.4 nm, with an average quality factor of 3650.
[0069] Example 3
[0070] A tunable micro-nano laser based on perovskite phase change material and a preparation method thereof.
[0071] Optionally, the substrate I is quartz glass; the distributed Bragg reflector II is composed of 8 pairs of titanium dioxide / silicon dioxide materials stacked together, with a total thickness of about 1.64 μm; the perovskite gain medium layer III is a 190 nm thick CsGeBr3 perovskite layer; and the top reflector IV is a 150 nm thick silver reflective layer.
[0072] The preparation flow chart of this embodiment can be found in Figure 2 , including the following steps:
[0073] Step 1: At room temperature, ultrasonically clean the substrate I quartz glass in acetone, isopropanol, and deionized water for 10 minutes. Dry with a nitrogen stream to ensure that there is no water stain on the surface of the cleaned wafer. Place the cleaned quartz glass in a UV ozone cleaning machine and clean it with oxygen plasma for 10 minutes.
[0074] Step 2: Use magnetron sputtering to alternately deposit 8 cycles of titanium dioxide / silicon dioxide dielectric layers to form the bottom distributed Bragg reflector II. Wipe the upper surface of the Bragg reflector II with ethanol, then rinse with deionized water, dry with nitrogen flow, and transfer to a UV ozone cleaner to be cleaned with oxygen plasma for 15 minutes to improve the adhesion to the perovskite film.
[0075] Step 3: A 0.8M precursor solution (the molar ratio of CsBr and GeBr2 is 1:1) was prepared in DMSO. The prepared solution was magnetically stirred overnight at 90°C in a nitrogen-filled glove box, then filtered with a polyvinylidene fluoride syringe filter (0.2μm) and placed on a hot plate at 70°C for 1 hour. 25μL of the precursor solution was drawn using a pipette and evenly dropped on the center of the distributed Bragg reflector II. The perovskite precursor solution was spin-coated onto the distributed Bragg reflector at a speed of 4000rpm for 70 seconds. 1mL of toluene was dropped on the distributed Bragg reflector 20s after the start of spin coating. Finally, it was placed on a hot plate at 90°C for thermal annealing for 8 minutes.
[0076] Step 4: The prepared sample with perovskite film (substrate I, Bragg reflector II, gain medium layer III) is quickly placed into the chamber of the electron beam evaporation equipment, and a 150nm silver layer is deposited on the perovskite film by electron beam evaporation as the top reflector IV.
[0077] The laser wavelength of the tunable micro-nano laser based on CsGeBr3 is adjustable between 533.1 and 550.4 nm, with an average quality factor of 2050.
[0078] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A tunable micro-nano laser based on perovskite phase change material, characterized in that: The tunable micro-nano laser comprises a substrate I and a distributed Bragg reflector II, a gain medium layer III and a reflector IV which are sequentially arranged on the substrate I from bottom to top; Wherein the gain medium III is a perovskite material having a crystal phase transition characteristic; The substrate I is a material that is transparent or has low loss to the pump light and the emitted light; The distributed Bragg reflector II is formed by alternating high refractive index layers and low refractive index layers, wherein a layer of high refractive index material and a layer of low refractive index material form a cycle; The gain medium layer III is a perovskite thin film layer with crystal phase transition characteristics, and the perovskite material has a spectrum tuning function in the laser resonant cavity; The reflecting mirror IV is composed of a metal film.
2. The tunable micro-nano laser based on perovskite phase change material according to claim 1, characterized in that: The logarithm of the high refractive index layer and the low refractive index layer of the distributed Bragg reflector II is 5-20, and the total thickness of the distributed Bragg reflector II is 0.5-2.5 μm; the reflectivity of the high reflective area of the formed Bragg reflector is not less than 99%, and the high reflective area should cover the photoluminescence spectrum area of the gain medium III.
3. The tunable micro-nano laser based on perovskite phase change material according to claim 1, characterized in that: By optimizing 1-3 pairs of alternating layers of high refractive index layers and low refractive index layers close to the substrate I of the bottom distributed Bragg reflector II, the transmittance of the pump light is made greater than 80%.
4. The tunable micro-nano laser based on perovskite phase change material according to claim 1, characterized in that: The distributed Bragg reflector II is designed such that the low refractive index layer contacts the gain medium III, and the high refractive index layer contacts the substrate I.
5. The tunable micro-nano laser based on perovskite phase change material according to claim 1, characterized in that: The material composition of the perovskite film layer is ABXn, wherein A is a monovalent cation, B is a divalent metal cation, X is an anion, and n is a positive integer.
6. The tunable micro-nano laser based on perovskite phase change material according to claim 1, characterized in that: The thickness of the perovskite thin film layer of the gain medium layer III is 100-500nm; The reflector IV is composed of a metal film with a thickness of 50-200nm; the reflector IV has high reflectivity and stable optical performance within the target wavelength range, and the reflectivity in the photoluminescence spectrum region of the gain medium III is not less than 99%.
7. The tunable micro-nano laser based on perovskite phase change material according to claim 1, characterized in that: The substrate I material is quartz, silicon dioxide, indium tin oxide ITO, polyimide PI, polyethylene glycol PET; The material of the high refractive index layer is one of tantalum pentoxide, hafnium dioxide, titanium dioxide, zinc sulfide, and gallium arsenide, and the material of the low refractive index layer is one of silicon dioxide, magnesium fluoride, and indium phosphide; In the material composition ABXn of the perovskite film layer, A is a cesium ion (Cs + ), methylamine ion (MA + ), formamidinium ion (FA + ), ethylamine ion (EA + ); B is lead ion (Pb 2+ ), tin ions (Sn 2+ ), Germanium ions (Ge 2+ ); X is a chloride ion (Cl - ), bromide ion (Br - ), iodide ion (I - ) The metal of the reflector IV metal film is one of gold, silver, aluminum and a mixture thereof.
8. A method for preparing a tunable micro-nano laser based on a perovskite phase change material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, pretreatment of substrate I; At room temperature, the substrate I was ultrasonically cleaned, blown dry with a nitrogen stream, and then placed in a UV ozone cleaning machine for oxygen plasma cleaning; Step 2, preparing a bottom distributed Bragg reflector II; Step 2.1, using magnetron sputtering or plasma enhanced chemical vapor deposition to alternately deposit multiple periods of high and low refractive index dielectric layers on the surface of substrate I to form a distributed Bragg reflector II, wherein the high refractive index layer is in contact with substrate I, and the uppermost layer of the distributed Bragg reflector II is a low refractive index layer; Step 2.2, after cleaning the upper surface of the Bragg reflector II, blow dry it with a nitrogen stream, and transfer it to a UV ozone cleaning machine for oxygen plasma cleaning; Step 3, preparing a perovskite gain medium layer III; A one-step solution deposition method is used to prepare a gain medium layer III on the surface of a Bragg reflector II, comprising the steps of: preparing a perovskite precursor solution, adding an anti-solvent by spin coating to induce crystallization, and thermal annealing treatment; Step 4, preparing top reflector IV; The top reflector IV is prepared on the surface of the gain medium layer III by magnetron sputtering, thermal evaporation or electron beam evaporation.
9. The method for preparing a tunable micro-nano laser based on perovskite phase change material according to claim 8, characterized in that: The step 3 of preparing the perovskite gain medium layer III is specifically as follows: The preparation process of the perovskite precursor solution is as follows: dissolving the precursor material in a solvent with a precursor concentration of 0.2-2M; stirring at 60-100° C. until the solution is completely clear, and filtering to remove impurities; The spin coating process of adding anti-solvent to induce crystallization by spin coating is as follows: uniformly dropping the precursor solution on the center of the substrate I; spin coating the perovskite precursor solution on the distributed Bragg reflector II at a speed of 3000-5500 rpm for 30-70 seconds; after the start of spin coating, adding anti-solvent to induce perovskite crystallization; and controlling the quality and thickness of the film by adjusting the rotation speed, time, drop amount and time of anti-solvent drop. The thermal annealing treatment is specifically as follows: after the spin coating and anti-solvent dripping processes are completed, the film is transferred to a heating table at 80-120° C. for thermal annealing for 5-15 minutes.
10. The method for preparing a tunable micro-nano laser based on perovskite phase change material according to claim 9, characterized in that: In the preparation process of the perovskite precursor solution, the precursor materials include PbI2 and MAI; In the spin coating process of adding anti-solvent to induce crystallization, the anti-solvent is added 5-20 seconds after the start of spin coating, and 0.1-1 ml of anti-solvent is added for every 20 μL-50 μL of precursor solution; the anti-solvent is one of toluene, chlorobenzene, and ether.
Citation Information
Patent Citations
Wavelength-adjustable perovskite micro-nano laser and preparation method thereof
CN117438885A
Preparation method of perovskite quantum dots
CN107500345A
Optical system and method of operating lithographic exposure apparatus
CN113589655A
Light-emitting device with white light conversion layer, electronic equipment and preparation method
CN116632140A
Green perovskite laser and preparation method thereof
CN116742473A
Cited By
Electrically-driven perovskite laser and preparation method thereof
CN121055157A
Surface enhanced Raman scattering substrate, preparation method and application thereof
CN121612863A
A surface-enhanced raman scattering substrate, a preparation method and application thereof
CN121612863B
Reflector applied to high power
CN121857120A